Spatio-temporal analysis of the earth's surface temperature in Marabá City, Pará, Brazil (Research, Society and Development, 2021)
The accelerated and disorganized development of urban centers has caused several impacts to these environments, especially with regard to the climatic aspects of cities. Combined with the reduction of vegetated areas to the detriment of the growth of built sites, the increase in urban temperatures has the consequence of the formation of the Heat Islands phenomena. Due to this, the present article aims to analyze space-time the terrestrial surface temperature of the city of Marabá in a temporal cut the months of July and August, from 1988 to 2018. The methodology used consisted of the collection, analysis and treatment of images from Landsat satellites 5 and 8, composed with land use data from the MapBiomas platform, preparation of maps, calculations and indices that enabled the identification and definition of urban heat islands and the characterization of land use dynamics. An average variation of maximum temperatures of 35.26% was observed, where the heat islands had an increase in formation mainly in the São Félix and Zona de Expansão Nova Marabá, while the vegetated areas had a decrease of 43.86 %, where these same urban centers presented a greater exchange of areas of Forest Formations for Urban Infrastructure. Thus, confirming the role of vegetation in regulating the surface temperature and the premise that waterproofed areas or areas with exposed soil are more likely to form urban heat islands.